Major histocompatibility complex class II (DR) antigen and costimulatory molecules on in vitro and in vivo activated human polymorphonuclear neutrophils - Sandilands, Gavin P (Blackwell Science Inc, 2006)
We have previously shown that normal human peripheral blood polymorphonuclear neutrophils (PMNs) contain cytoplasmic ‘stores’ of three key molecules normally associated with antigen presentation and T-cell costimulation, i.e. major histocompatibility complex class II (DR) antigen, CD80 (B7-1) and CD86 (B7-2). These cytoplasmic molecules were found to translocate to the cell surface within a few minutes following cross-linking (X-L) of Mac-1: an early neutrophil activation signal. In this study we have compared X-L of Mac −1 in parallel with four other well documented in vitro neutrophil activators: phorbol myristate acetate, N-formyl methionyl leucyl phenylalanine, lipopolysaccharide, and phagocytosis of immunoglobulin G–Latex particles. In addition, we have used paired samples of neutrophils obtained from peripheral blood (as a control) and synovial fluid from patients with rheumatoid arthritis as a source of in vivo activated cells. With the exception of phagocytosis, all activators resulted in the rapid (within 30 min) generation of two populations of activated neutrophils (designated P1 and P2) based on flow-cytometry measurements of size, granularity and phenotype. Significant up-regulation of DR and costimulatory molecules was observed, predominantly on P2 cells, with all activators except phagocytosis. CD80 and CD86 were noted to respond to the various activation signals in a different pattern suggesting that their intracellular granule location may be different. Dual-staining confocal laser microscopy studies showed that CD80 is largely confined to secretory vesicles (SVs) while CD86 appears to have a much wider distribution being found in SVs and within secondary (specific) and primary (azurophilic) granules. Increased surface expression of these antigens was also observed on P2 synovial fluid neutrophils appearing as large heterogeneous clusters on the cell surface when visualized by confocal laser microscopy.